1985
DOI: 10.1111/j.1533-8525.1985.tb00225.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exports, Public Debt, and Development on Income Inequality

Abstract: Classical economics and most modernization theorists hold that a curvilinear relationship exist between income inequality and development level. In this article that relationship is tested. In addition, it is hypothesized that exports and debt as percentages of gross domestic product increases individual income inequality. Regression analyses with controls for development and time were used to test these relationships (N=28 at two time periods). To test these hypotheses with additional data a panel cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
2
26
0
4
Order By: Relevance
“…Export-oriented production for the world market creates sector dualism in which the primarily foreignowned export segment of the economy monopolizes internal capital and repatriates profi ts, stagnating the domestic sector. Th e empirical evidence indicates that large export sectors are positively related to income inequality (Stack 1980;Prechel 1985). Th e considerably more capital-intensive nature of export production results in higher returns to capitalists at one end and the underemployment of the indigenous labor force at the other.…”
Section: Theoretical Perspectives On Crossnational Income Inequalitymentioning
confidence: 99%
See 3 more Smart Citations
“…Export-oriented production for the world market creates sector dualism in which the primarily foreignowned export segment of the economy monopolizes internal capital and repatriates profi ts, stagnating the domestic sector. Th e empirical evidence indicates that large export sectors are positively related to income inequality (Stack 1980;Prechel 1985). Th e considerably more capital-intensive nature of export production results in higher returns to capitalists at one end and the underemployment of the indigenous labor force at the other.…”
Section: Theoretical Perspectives On Crossnational Income Inequalitymentioning
confidence: 99%
“…While size of the export sector has been found to be associated with inequality, other dependency measures such as commodity concentration and debt service have not been found to be signifi cantly related to income inequality (Weede and Tiefenbach 1981;Prechel 1985;Chan 1989). However, dependency scholars stress the dynamic nature of global capitalism, and how the changing character of capitalist exchange on a global scale is coupled with alterations in the nature of the relations of dependency among the participants.…”
Section: Linda Beer and Terry Boswell 33mentioning
confidence: 99%
See 2 more Smart Citations
“…Bornschier and Ballmer-Cao (1979) found that MNC-penetration increases levels of income inequality through its effects on the power distribution of a country. Galtung (1971) and Prechel (1985) found that trade dependence is positively related to income inequality. However, Chan (1989) found that trade dependence has little influence on income inequality, and Weede and Tiefenbach (1981) found little support for the contention that trade dependence and foreign investment dependence exacerbate income inequality.…”
Section: Conflicting Results Of Previous Studiesmentioning
confidence: 99%